2021
DOI: 10.1177/14752409211060901
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics that Define an Exceptional International School According to Stakeholder Perspectives. A Thai Case Study

Abstract: Research in international schools has lagged behind the growth of such schools (Lee et al, 2012). This paper offers support to international school leaders by identifying the ten most important characteristics of international schools as reported by three significant stakeholder groups (administrators/teachers, parents and students) in one case study international school. An initial phase utilised a Delphi framework whereby interviews led to the identification of 68 separate items, ranging from school ethos to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In Thai society, most parents tend to travel to pick up and drop off the students at school regularly, in contrast with the Western countries in which students travel to and from school on their own. 24,25 In addition, in a closer examination of the relationship between operation time and criteria-based dispatch level, it was found that motorcycle ambulances can reach patients with resuscitated level (red) from 6:00AM-9:00AM and 3:00PM-6:00PM faster than traditional van ambulances. This may be due to EMS personnel being trained to respond quickly in this type of patients; the example of patients categorized as red following criteria-based dispatch in this study were unresponsive patients, seizure, respiratory distress, shock, air-way obstruction, or major trauma, all which need immediate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In Thai society, most parents tend to travel to pick up and drop off the students at school regularly, in contrast with the Western countries in which students travel to and from school on their own. 24,25 In addition, in a closer examination of the relationship between operation time and criteria-based dispatch level, it was found that motorcycle ambulances can reach patients with resuscitated level (red) from 6:00AM-9:00AM and 3:00PM-6:00PM faster than traditional van ambulances. This may be due to EMS personnel being trained to respond quickly in this type of patients; the example of patients categorized as red following criteria-based dispatch in this study were unresponsive patients, seizure, respiratory distress, shock, air-way obstruction, or major trauma, all which need immediate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of British international schools among local national parents can be seen as reflective of their desire for their children to go to universities overseas and become members of the global middle class, given the perceived cultural capital and education such schools are believed to provide (Bunnell 2019; Fahey and Ganguly, 2021; Poole, 2020; Rush, 2014). Equally, a ‘British style’ of schooling is particularly valued, these schools emphasising their ‘Britishness’ in their imagery and marketing (Bunnell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%